An overview of a water quality monitoring in water supply scheme: a case study on iron present in groundwater wells in vallipuram, jaffna - Saravanan, S.; Mikunthan, T .; Gunaalan, K. (University of Jaffna, 2015)
Drinking water is one of the basic needs of life and essential for survival. Iron is a harmless element in the groundwater, though sometimes annoying element present in water supplies. Iron is primarily component of groundwater with the characteristic of staining properties, although high levels can impart a bittersweet or metallic taste to drinking water. In case of Jaffna Peninsula, it is fully depend on groundwater for drinking, agriculture and industry. The quality of groundwater is getting deteriorate due to many factors. The National Water Supply and Drainage Board (NWS&DB) have several schemes to supply the water where water under scarce and unacceptable quality.Under the Asian Development Bank fourth project, Point Pedro water supply scheme has been started with the construction of four collector wells as a water source. Each well is having 150 m long slotted stainless steel lateral pipes to increase the capacity. Currently the concentration of iron plays the crucial role in supply of the scheme. Prior to construction of wells there was no any issues observed and the Iron concentration was varied 0.00 to 0.22 mg/L during bore hole testing in 2010. Later in 2012 the iron concentration was observed as 0.76 mg/L, also the water sample contained brownish suspended matters and sediments. But in 2014 after completion of well construction the situation was totally altered and the maximum iron concentration pointed as 4.6 mg/L and also brownish scum was observed in those wells due to the iron bacteria activity. The increasing trend of iron concentration was observed in the wells. Still the adjacent wells don’t have iron problems. Hence NWS&DB did several well cleaning, lateral pipe cleaning works, shock chlorination and continuous pumping to improve the quality as management practices and now the iron concentration was reduced up to accepted level as 0.1 to 0.2 ppm in distributed water.